From non-human to human primates: a translational approach to enhancing resection, safety, and indications in glioma surgery while preserving sensorimotor abilities - Gambaretti, Matteo; Viganò, Luca; Gallo, Matteo; Pratelli, Giovanni; Sciortino, Tommaso; Gay, Lorenzo; Conti Nibali, Marco; Gallotti, Alberto Luigi; Tariciotti, Leonardo; Mattioli, Luca; Bello, Lorenzo; Cerri, Gabriella; et al. (Frontiers in Integrative Neuroscience, 2025)
Since the pivotal studies of neurophysiologists in the early 20th century, research on brain functions in non-human primates has provided valuable insights into the neural mechanisms subserving neurological function. By using data acquired on non-human primates as a reference, important progress in knowledge of the human brain and its functions has been achieved. The translational impact allowed by this scientific effort must be recognized in the implementation of the current surgical techniques particularly in support of the neurosurgical approach to brain tumors. In the surgical treatment of brain tumors, the ability to maximally extend the resection allows an improvement in overall survival, progression-free survival, and quality of life of patients. The main goal, and, at the same time, the main challenge, of oncological neurological surgery is to avoid permanent neurological deficit while reaching maximal resection, particularly when the tumor infiltrates the neural network subserving motor functions. Brain mapping techniques were developed using neurophysiological probes to identify the areas and tracts subserving sensorimotor function, ensuring their preservation during the resection. During the last 20 years, starting from the classical “Penfield” technique, brain mapping has been progressively implemented. Among the major advancements was the introduction of high-frequency direct electrical stimulation. Its refinement, along with the complementary use of low-frequency stimulation, allowed a further refinement of stimulation protocols. In this narrative review, we propose an analysis of the process through which the knowledge acquired through experiments on non-human primates influenced and changed the current approach to neurosurgical procedures. We then describe the main brain mapping techniques used in the resection of tumors located within sensorimotor circuits. We also detail how these techniques allowed the acquisition of new data on the properties of areas and tracts underlying sensorimotor control, in turn fostering the design of new tools to navigate within cortical and subcortical areas, that were before deemed to be “sacred and untouchable.”